EFFECTIVENESS OF USING PROBLEM BASED LEARNING MODELS ABOUT CRITICAL THINKING IN LEARNING GEOGRAPHY STUDENTS OF CLASS X IS 2 IN SMA 1 BANYUDONO - Rosyida, Yasyfa Nafi (Pendidikan Geografi, 2014)
This research aims to determine the effectiveness of using Problem Based Learning models about critical thinking in learning geography students of class X IS 2 in SMA 1 Banyudono.This research is quasi-experimental study. The design study is a pretest-posttest control group. These subjects are students of class X and X IS 1 IS 2 SMA 1 Banyudono. Class X IS 2 is an experimental class were treated to a model Problem Based Learning, while class X IS 1 as the control class with the conventional model. The research data was collected using tests and observation. Hypothesis testing using t-test of the average value of the posttest.The results of t-test showed that t values = 3.152> t table = 2.000, meaning that the difference is significan. The difference showed that the average value of post test experimental class is 73,75 and the average value of post test control is 62,73. The average value of post test experimental class is greater than the average value of post test control. The conclusion of this research is the use of a model problem based learning in geography learning is more effective than the conventional model of critical thinking learners.